Comparison of Perioperative Safety and Recovery Profiles between Low-Pressure and Standard-Pressure Laparoscopic Cholecystectomy - Muhammad Asjad, Abdul Ghaffar Arain, Luqman Ali Bajwa, Nauman Ali, Mohammad Ali Naper (Pakistan Journal of Medical & Health Sciences, 2023)
Background: To compare perioperative safety and recovery outcomes between low-pressure (8–10 mmHg) and standard-pressure (12–15 mmHg) laparoscopic cholecystectomy. Methods: This prospective comparative study included 73 patients undergoing elective laparoscopic cholecystectomy from June 2022 to June 2023. Patients were randomized into two groups: low-pressure (n = 36) and standard-pressure (n = 37). Intraoperative safety parameters, postoperative pain scores, analgesic use, recovery milestones, complications, and patient satisfaction were recorded and analyzed. Results: Both groups were similar in baseline demographics and comorbidities. Peak end-tidal CO₂ was lower in the low-pressure group (p = 0.002) without prolonging operative time. Postoperative pain scores at 6 hours were significantly reduced (p = 0.01) in the low-pressure group, with lower opioid requirements (p = 0.002) and less shoulder-tip pain (p = 0.03). Early ambulation and shorter hospital stays were also noted (p = 0.04). Complication rates were low and comparable between groups. Conclusion: Low-pressure laparoscopic cholecystectomy offers superior postoperative comfort and earlier recovery without compromising intraoperative safety. It may be considered a safe alternative to standard-pressure pneumoperitoneum in suitable patients. Keywords: Laparoscopic cholecystectomy, low-pressure pneumoperitoneum, postoperative pain, recovery time, gallstone surgery, intraoperative safety